Soil-Gas Radon as a Possible Earthquake Precursor: A Case Study from the Khlong Marui Fault Zone, Southern Thailand - Pattama Pispak; Helmut Dürrast; Tripob Bhongsuwan (Agriculture and Natural Resources, 2010)
This study was initiated to measure the radon concentration in soil over time and then to analyze possible variations of the radon data with respect to potential earthquake precursors for the Klong Marui fault zone (KMFZ) and related faults in Southern Thailand. An automatic soil gas radon monitoring system (12 Feb-2 May 2007) and a short-period seismometer (14 Jan-21 Apr 2007) were installed in Thap Put district, Phang Nga province in the KMFZ. Two significant positive radon anomalies were observed during the short period of study, on 18 Feb and 1 Mar 2007, and an increase in local and regional earthquake activity was observed several days after each radon anomaly. It was concluded that there was a possibility of using the radon monitoring in soil gas as a possible method for providing earthquake warnings in the study area.